Implementasi Model Pembelajaran Kontekstual di Sekolah Dasar - Lipiah, Dede; Septianti, Nabillah; Yuwono, Rachmat; Atika, Rindi (TSAQOFAH, 2022)
The teaching and learning process is the most important part in education, in which there are teachers as teachers and students who are learning. The teaching and learning process occurs when there is interaction between students and the learning environment arranged by the teacher to achieve teaching goals. The learning process requires the right method. Errors in using the method can hinder the achievement of the desired educational goals. Therefore, in improving the quality of the teaching and learning process, teachers need to apply learning models, one of which is Contextual Teaching and Learning (CTL). In Contextual Teaching and Learning (CTL) students learn through experience, remembering that knowledge is not from a fact and a concept that is ready to be accepted, but something that must be constructed by students. With this concept, it is hoped that learning outcomes are expected to be more meaningful for students. Because the learning process takes place naturally in the form of student activities working and experiencing, not transferring knowledge from teacher to student. The learning process is more important than the results.